1985
DOI: 10.1136/jech.39.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Serological hepatitis A virus infections and ratio of clinical to serological infections in a controlled trial of pre-exposure prophylaxis with immune serum globulin.

Abstract: All cases of clinically identified hepatitis that occurred during military service were routinely and obligatorily admitted to civilian hospitals and were routinely tested for hepatitis B surface antigen.4 Men serve a compulsory period of three years and women two years. A proportion of subjects served longer than the compulsory period and a relatively smaller 117

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These rates are obviously influenced by a v a r i e t y of climatic and sociohygienic factors, including the effectiveness of immunoglobulin prophylaxis. A ntlmber of serial cross-sectional studies carried out in areas in which hepatitis A is endemic have revealed that the annual increment of anti--HAV positives varied from lto 3% (10,12). though occasionally it can be as high as 35% (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These rates are obviously influenced by a v a r i e t y of climatic and sociohygienic factors, including the effectiveness of immunoglobulin prophylaxis. A ntlmber of serial cross-sectional studies carried out in areas in which hepatitis A is endemic have revealed that the annual increment of anti--HAV positives varied from lto 3% (10,12). though occasionally it can be as high as 35% (16).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of immunoglobulin in preventing hepatitis A infection, either overt (7, 6 ) o r s u bclinical (12), has been repeatedly demonstrated.…”
mentioning
confidence: 99%